Associations between blood selenium and serum neurofilament light chain: results of a nationwide survey - Liao, Yayun; Zhou, Kejian; Lin, Baoquan; Deng, Shan; Qin, Lu; Weng, Baohui; Yang, Hong; Pan, Liya (Frontiers in Neurology, 2025)
BackgroundSelenium (Se) is essential for many nervous system functions including memory, cognition and coordination, which has also been linked to a variety of neurological disorders, such as epilepsy, Alzheimer’s disease (AD) and Parkinson’s disease (PD). Serum neurofilament light chain (sNfL) is a biomarker of neurologic diseases. Studies on the relationship between blood Se and sNfL are limited.MethodsThe National Health and Nutrition Examination Survey (NHANES) 2013–2014 data were employed to perform multivariate linear regression analysis and smooth curve fitting in order to investigate the relationship between blood Se and sNfL. Utilizing subgroup analyses and interaction tests, the stability of this relationship between populations was evaluated.ResultssNfL and blood Se had an inverse relationship in 1,036 individuals who were older than 20. According to the fully adjusted model, the sNfL decreased by 54.75 pg./mL for every unit increase in log blood Se [β = −54.75, 95% CI (−75.36, −34.14)]. The sNfL of individuals in the highest blood Se quartile decreased by 3.4 pg./mL in comparison to those in the lowest quartile [β = −3.40, 95% CI (−6.47, −0.32)]. This inverse association was more significant in those who were younger than 60 years old, male, normal weight, had a history of smoking and drinking.ConclusionBlood Se is inversely associated with sNfL in American adults. Our findings indicate that blood Se may have a potential protective effect against neuronal damage.